Surface analysis in additive manufacturing: a systematic literature review regarding powder bed fusion processes - Grimm, Tobias; Hantke, Nick; Iusupova, Alsu; Sehrt, Jan T (Surface topography metrology and properties, 2025)
The analysis of surface effects in powder bed fusion additive manufacturing is the subject of intensive research activities. The aim of this paper is to provide an overview of the current state of knowledge and to gain a comprehensive understanding of this subject area. The paper is intended to enable researchers to select specific articles for their own further research context. In addition, a bibliometric analysis validates the data base. A discussion of the findings suggests that the criticality of the surface should be considered as a quality factor in the field of additive manufacturing by powder bed fusion processes. An accurate and reliable measurement is crucial for predicting component quality. There is a clear trend from two-dimensional measurements to three-dimensional measurements. Conducting comprehensive research is essential to improve the reliability and comparability of measurement results and to promote broad acceptance and application of this technology in the industry.